Expression of calcium-binding proteins and selected neuropeptides in the human, chimpanzee, and crab-eating macaque claustrum - Pirone, Andrea; Castagna, Maura; Granato, Alberto; Peruffo, Antonella; Quilici, Francesca; Cavicchioli, Laura; Piano, Ilaria; Lenzi, Carla; Cozzi, Bruno (Frontiers in Systems Neuroscience, 2014)
The claustrum is present in all mammalian species examined so far and its morphology, chemoarchitecture, physiology, phylogenesis and ontogenesis are still a matter of debate. Several morphologically distinct types of immunostained cells were described in different mammalian species. To date, a comparative study on the neurochemical organization of the human and non-human primates claustrum has not been fully described yet, partially due to technical reasons linked to the postmortem sampling interval. The present study analyzes the localization and morphology of neurons expressing parvalbumin (PV), calretinin (CR), NPY, and somatostatin (SOM) in the claustrum of man (# 5), chimpanzee (# 1) and crab-eating monkey (#3). Immunoreactivity for the used markers was observed in neuronal cell bodies and processes distributed throughout the anterior-posterior extent of human, chimpanzee and macaque claustrum. Both CR- and PV-immunoreactive (ir) neurons were mostly localized in the central and ventral region of the claustrum of the three species while SOM- and NPY-ir neurons seemed to be equally distributed throughout the ventral-dorsal extent. In the chimpanzee claustrum SOM-ir elements were not observed. No co-localization of PV with CR was found, thus suggesting the existence of two non-overlapping populations of PV and CR-ir interneurons. The expression of most proteins (CR, PV, NPY), was similar in all species. The only exception was the absence of SOM-ir elements in the claustrum of the chimpanzee, likely due to species specific variability. Our data suggest a possible common structural organization shared with the adjacent insular region, a further element that emphasizes a possible common ontogeny of the claustrum and the neocortex.